Pengaruh Penggunaan Poly Aluminium Chloride (PAC) terhadap Air Limbah Budidaya Ikan Nila - Ima Yudha Perwira; Devi Ulinuha (Current Trends in Aquatic Science, 2023)
Nile Tilapia culture is potential to provide waste containing high organic matter and turbidity. Therefore, it is important to perform waste water treatment on this culture to reduce the environmental polution risk caused by this activity. This study aimed to reduce the organic material amount and other substances in the waste water of Nile Tilapia culture by using Poly Aluminium Chloride (PAC). The study was performed experimentally by using 4 treatments: PAC 0 mg/L (control), PAC 10 mg/L, PAC 15 mg/L, and PAC 20 mg/L. Total organic matter (BOT) was measured using permanganate method, water turbidity was measures using Turbidimeter, total suspended solids (TSS) was measured using Gravoimetric method, ammonia was measured using Nessler method, nitrite was measured using NED dihydrochloride-Sulfanilamide method, nitrate was measured using cadmium-reduction method, and phosphate was measured using Ascorbic acid method. The study showed that PAC 15 and 20 mg/L drastically reduced the BOT and turbidity (>30%), while the reduction of TSS was not more than 25%. Ammonia, nitrite, nitrate, and phosphate were not influenced by the application of PAC.